Pengembangan Sekolah SMA/SMK Yapim Taruna Marelan Dengan Sistem Informasi Akademik Berbasis Web - Sri Wahyuni; Randi Rian Putra; Cendra Wadisman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Academic information system is one of the systems used in managing academic data that is applied in computer technology. This research aims to develop Yapim Taruna Marelan High School / Junior High School with a web-based academic information system, because it is related to those in Yapim Junior High School Maruna still using a manual-based academic system. High School / Junior High School Yapim Taruna Marelan, then formulates the problems that exist in this school, merging data, doing system design, and the final implementation program. The benefit of this research is to provide convenience from the school in processing data, both school data, teachers, students and others, academic information systems can provide facilities for schools, teachers and school citizens in accessing information about the school, and can be used as a media for delivering more effective and efficient information that can be accessed anywhere and anytime online, both for schools, students and the community.